Structural and functional indicators of the heart of patients with ischemic heart disease and type 2 diabetes mellitus. Rhythmoinotropic response isolated myocardium at different levels of glycated hemoglobin - D. S. Kondratieva (Endocrinology Research Centre, 2021)
BACKGROUND: Adequate glycemic control can significantly reduce the risk of developing cardiovascular events. However, until now, glycaemic targets in aged patients remain a subject of discussion, especially in the conditions of the combined development of Type 2 Diabetes Mellitus (T2DM) and ischemic heart disease (IHD).AIMS: To examine the structural and functional heart parameters in patients with IHD associated with T2DM and the rhythmoinotropic responses of their isolated myocardium depending on glycated hemoglobin level.MATERIALS AND METHODS: The study included 44 patients with a diagnosis of "chronic IHD associated with T2DM", of which 2 groups were formed. Patients with glycated hemoglobin level (HbA1c) <8% were included in the 1st group, and patients with HbA1c ≥8% were included in the 2nd group. The structural and functional heart parameters obtained with ultrasonography, and the rhythmoinotropic responses of myocardium in patients ex vivo were analyzed using the right atrial appendage fragments obtained during elective coronary artery bypass graft. The inotropic response of muscle strips at a basic stimulation frequency of 0,5 Hz to testing influences was assessed. An extrasystolic test and post-rest test were performed.RESULTS: It was found that extrasystolic contractions of isolated myocardial strips in patients of the 2nd group appeared at shorter extrasystolic intervals, which indicates a greater excitability of the myocardium in patients of this group. Postextrasystolic muscle contractions in patients of the 2nd group had significant potentiation. The amplitude of the muscle strips contractions in patients of both groups was potentiative after short rest periods. However, with an increase in the rest duration, potentiation of contractions was observed only in the group with a higher HbA1c level. According to the ultrasonography data, it was found that the values of the endsystolic and diastolic volumes, the interventricular septum thickness and the left ventricular (LV) myocardium mass were significantly lower in the patients of the 1st group compared with the corresponding indicators in the patients of the 2nd group. The early LV filling velocity (peak E) was significantly lower in the patients of the 1st group, which indicates a slower LV relaxation. At the same time, the rapid LV filling velocity did not have a significant intergroup difference, but this indicator exceeded the reference values in both groups.CONCLUSIONS: With a moderately increased glycemic level (9,2 [8,0; 10,3]%), the structural and functional heart parameters are preserved both at the level of the isolated myocardial tissue and at the level of the whole heart.